Sulfonamide / sulfonamide ester additive and application thereof in sodium-ion battery electrolyte
By introducing sulfonamide/sulfonamide ester additives into the sodium ion battery electrolyte, the problem of SEI membrane in the sodium ion battery electrolyte system is solved, and the electrochemical stability and cycle life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411831055.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
The existing sodium ion battery electrolyte system is difficult to form a stable solid electrolyte interface (SEI) film on the electrode surface, resulting in poor electrochemical performance and short cycle life.
A sulfonamide/sulfonamide ester additive was designed and synthesized. By introducing amine groups, F-element-containing groups and sulfonate groups, the composition of the electrolyte is optimized and the formation and stability of the SEI film is promoted.
It significantly improves the electrochemical stability of sodium ion batteries, extends the cycle life, and improves the safety of the batteries, solving the problems of poor rate performance and short cycle life in traditional electrolyte systems.
Smart Images

Figure CN119725738A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery electrolyte additives, in particular to a sulfonamide / sulfonamide ester additive and application thereof in sodium ion battery electrolytes. Background Art
[0002] Sodium is abundant in the earth's crust and evenly distributed, which has the advantages of abundant resources and low cost for the development of new sodium-ion battery energy storage systems. In addition, since sodium ions do not form alloys with aluminum at low voltages, cheap aluminum foil can be used as current collectors for both the positive and negative electrodes of sodium-ion batteries. From the perspective of raw material costs, the cost of sodium-ion batteries can be reduced by 30%-40%. Lithium and sodium belong to the same main group elements. Sodium-ion batteries and lithium-ion batteries have similar working principles, and the battery production processes are highly similar. Therefore, the development of high-performance sodium-ion battery electrochemical energy storage technology with cost and resource advantages is expected to replace some application scenarios of lead-acid batteries and lithium-ion batteries in the future, and realize the sustainable development of low-cost large-scale energy storage technology.
[0003] In recent years, the positive and negative electrode materials of sodium-ion batteries have been widely developed and explored. The capacity of related materials is comparable to that of lithium-ion battery electrode materials, but the matching electrolyte system is still being explored. In the existing electrolyte system, sodium-ion batteries cannot form a stable solid electrolyte interface (SEI) film on the electrode surface like lithium-ion batteries, which makes the electrochemical performance of sodium-ion batteries unsatisfactory. How to optimize the "electrolyte system" so that it can form a stable and dense SEI film on the electrode surface, thereby obtaining a sodium-ion battery with a long cycle life, is a bottleneck problem that needs to be solved urgently in this field.
[0004] Electrolyte additives have an important influence on the formation, structure and composition of the SEI film, thereby affecting the electrochemical performance of the battery. Currently, commercial electrolyte additives include fluoroethylene carbonate (FEC) and vinylene carbonate (VC). However, this series of electrolyte additives have problems such as easy gas production during the cycle, poor high-temperature performance and easy combustion, and have limited improvement on the performance of sodium-ion batteries. Therefore, it is necessary to design suitable additive molecules that can preferentially decompose to form a uniform and stable SEI film, thereby greatly improving the electrochemical performance of sodium-ion batteries. Studies have shown that the introduction of fluoroalkyl groups into the electrolyte can significantly improve the oxidation and reduction stability of the electrolyte; the amine group can remove trace HF / H in the battery. 2 O; the sulfonate group can improve the ionic conductivity of the electrolyte, which is beneficial to the construction of a low-impedance SEI film; through reasonable molecular design, the above functional groups are unified into one additive molecule, which is conducive to the formation of a uniform and stable SEI film, thereby significantly improving the electrochemical stability of sodium-ion batteries and achieving long-life sodium-ion battery application scenarios.
[0005] In view of the above problems, the present invention designs and synthesizes an electrolyte additive system suitable for long-life sodium ion batteries. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a sulfonamide / sulfonamide ester additive and its application in sodium ion battery electrolyte.
[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0008] One of the objects of the present invention is to provide a sulfonamide / sulfonamide ester additive, which is a compound of the structural formula shown in formula (I):
[0009]
[0010] Where: R 1 is one of a C1-C3 fluoroalkyl group or a fluorinated ether group;
[0011] R 2 and R 3 Each is independently one of a C1-C3 alkyl group or a fluorinated alkyl group.
[0012] Furthermore, the R 1 One of the following groups:
[0013]
[0014] R 2 and R 3 One of the following groups:
[0015]
[0016] Preferably, the sulfonamide / sulfonamide ester additive is one of the following compounds 1 to 75:
[0017]
[0018]
[0019] A second object of the present invention is to provide a sulfonamide / sulfonamide ester additive for use in sodium ion battery electrolyte.
[0020] Specifically, a sulfonamide / sulfonamide ester additive having a volume fraction of 0.1% to 10% is added to the sodium ion battery electrolyte.
[0021] Compared with the prior art, the sulfonamide / sulfonamide ester additive of the present invention can remove trace hydrofluoric acid and water in the battery by introducing an amine group; the introduction of a group containing the F element can form a dense passivation protective film on the surface of the electrode material to isolate the electrolyte and the electrode material from further reaction; the introduction of the sulfonate group can improve the ionic conductivity of the electrolyte and form a low-impedance electrode-electrolyte interface film, thereby obtaining a sodium ion battery electrolyte additive system with both long life and high safety, and specifically solving the bottleneck problems of poor electrolyte rate performance and short cycle life in traditional carbonate and ether electrolyte systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the long cycle performance diagram of NFVP||Na battery in ED and EDF electrolytes;
[0023] Figure 2 This is the rate performance diagram of NFVP||Na battery in ECD and ECDF electrolytes;
[0024] Figure 3 The long cycle performance diagram of NFM111|Na battery in NFS and Baseline electrolytes;
[0025] Figure 4 The rate performance diagram of NFM111|Na battery in BE and BEM electrolytes;
[0026] Figure 5 This is the long cycle performance diagram of NFM111||HC soft pack battery in TMS and Baseline electrolyte;
[0027] Above Figure 1-Figure 5 The symbols “△” and “○” in the chart represent the coulombic efficiency of the battery, and the symbols “▲” and “●” represent the capacity of the battery. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0029] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available; and the following examples take several typical compounds as examples of sulfonamide / sulfonamide ester additives.
[0030] Example 1
[0031] 1) Preparation of compound 7: Add an appropriate amount of dichloromethane to a double-necked round-bottom reaction bottle under anhydrous and oxygen-free conditions, slowly add 2eq triethylamine and 1.2eq N-ethyl-2,2,2-trifluoroethylamine in sequence under stirring conditions, then slowly drop 1eq trifluoroethylsulfonyl chloride under ice-water bath conditions, and react at room temperature for 14h. After the reaction is completed, wash with 0.5M hydrochloric acid and separate the liquids, collect the organic phase, wash the liquids twice with saturated brine, take the organic phase; then dry with anhydrous sodium sulfate, filter, rotary evaporate, and distill under reduced pressure to obtain high-purity compound 7; the reaction formula is:
[0032]
[0033] The prepared compound 7 solution was placed in a glove box at 25° C. with a water content and an oxygen content less than 0.01 ppm, and dried with molecular sieves for 72 hours to remove moisture and obtain high-purity compound 7.
[0034] Example 2
[0035] 1) Preparation of compound 18: Under anhydrous and oxygen-free conditions, add an appropriate amount of dichloromethane to a double-necked round-bottom flask, slowly add 2eq of triethylamine and 1.2eq of N-methylmethylamine in sequence under stirring, then slowly drop 1eq of trifluoroethanesulfonyl chloride under ice-water bath conditions, and react at room temperature for 14h. After the reaction is completed, wash the separated liquid with 0.5M hydrochloric acid, collect the organic phase, wash it with saturated brine and separate it twice, then dry it with anhydrous sodium sulfate, filter, rotary evaporate, and distill under reduced pressure to obtain compound 18; the reaction formula is:
[0036]
[0037] The prepared compound 18 solution was placed in a glove box at 25° C. with a water content and an oxygen content less than 0.01 ppm, and dried with molecular sieves for 72 hours to remove moisture and obtain high-purity compound 18.
[0038] Example 3
[0039] Preparation of compound 22: Under anhydrous and oxygen-free conditions, add an appropriate amount of dichloromethane to a double-necked round-bottom flask, slowly add 2eq triethylamine and 1.2eq N-ethyl-2,2,2-trifluoroethylamine in sequence under stirring, then slowly drop 1eq trifluoroethylsulfonyl chloride under ice-water bath conditions, and react at room temperature for 14h. After the reaction is completed, wash the separated liquid with 0.5M hydrochloric acid, collect the organic phase, wash it with saturated brine and separate it twice, then dry it with anhydrous sodium sulfate, filter, rotary evaporate, and distill under reduced pressure to obtain compound 22; the reaction formula is:
[0040]
[0041] The prepared compound 22 solution was placed in a glove box at 25° C. with a water content and an oxygen content less than 0.01 ppm, and dried with molecular sieves for 72 hours to remove moisture and obtain a high-purity compound 22.
[0042] Example 4
[0043] 1) Preparation of compound 45: Add a tetrahydrofuran solution of thionyl chloride under an ice-water bath under anhydrous and oxygen-free operation, then slowly drop 1eq of N-methylethylamine, slowly return to room temperature, and react for 1h, then remove excess solvent from the solution system 1 after the reaction by a rotary evaporator to obtain a reaction intermediate; take a new reaction bottle, add an appropriate amount of sodium hydride to a double-necked round-bottom flask, seal it with a rubber stopper, and slowly evacuate / fill with argon for three cycles. Slowly add an appropriate amount of tetrahydrofuran under an ice-water bath, slowly add trifluoroethanol under stirring, react at room temperature for 2h, then slowly drop the crude product of the reaction in the first step, stir vigorously while dropping, and react at room temperature for 12h after the dropwise addition. After the reaction is completed, slowly drop deionized water into the flask to completely quench the sodium hydride, then filter, and remove most of the tetrahydrofuran by rotary evaporation, wash the remaining organic matter with 0.5M hydrochloric acid, collect the organic phase, and then wash it twice with saturated brine. The obtained organic matter was distilled under reduced pressure for several times, and then distilled under reduced pressure again after removing water with sodium to obtain compound 45; the reaction formula is:
[0044]
[0045] The prepared compound 45 solution was placed in a glove box at 25° C. with a water content and an oxygen content less than 0.01 ppm, and dried with molecular sieves for 72 hours to remove moisture and obtain a high-purity compound 45.
[0046] Example 5
[0047] 1) Preparation of compound 53: Add a tetrahydrofuran solution of thionyl chloride under an ice-water bath condition under anhydrous and oxygen-free operation, then slowly drop 1eq of N-methylpropylamine, slowly return to room temperature, and react for 1h, then remove excess solvent from the solution system 1 after the reaction using a rotary evaporator to obtain a reaction intermediate; then take a new reaction bottle, add an appropriate amount of sodium hydride to a double-necked round-bottom flask, seal it with a rubber stopper, and slowly evacuate / fill with argon for three cycles. Slowly add an appropriate amount of tetrahydrofuran under an ice-water bath, slowly add 2,2,3,3,3-pentafluoropropane-1-ol under stirring conditions, react at room temperature for 2h, then slowly drop the crude product of the reaction in the first step, stir vigorously while dropping, and react at room temperature for 12h after the dropwise addition. After the reaction is completed, slowly drop deionized water into the flask to completely quench the sodium hydride, then filter, rotary evaporate to remove most of the tetrahydrofuran, wash the remaining organic matter with 0.5M hydrochloric acid, collect the organic phase, and then wash it twice with saturated brine. The obtained organic matter was distilled under reduced pressure for several times, and then distilled under reduced pressure again after removing water with sodium to obtain compound 53; the reaction formula is:
[0048]
[0049] The prepared compound 53 solution was placed in a glove box at 25° C. with a water content and an oxygen content less than 0.01 ppm, and dried with molecular sieves for 72 hours to remove moisture and obtain a high-purity compound 53.
[0050] Test Case
[0051] Exemplarily, the high-purity compound 7, high-purity compound 18, high-purity compound 22, high-purity compound 45 and high-purity compound 53 prepared in Examples 1 to 5 are used to prepare the corresponding sodium ion battery electrolytes:
[0052] Electrolyte containing high-purity compound 7
[0053] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.168 g of sodium hexafluorophosphate and dissolve it in 1 mL of a solution of ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate (volume ratio of 5:5:1) and stir overnight to fully dissolve and mix well to prepare a 1 mol L -1 Sodium ion battery electrolyte (denoted as ED);
[0054] 2) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, 10 μL of high-purity compound 7 was mixed with 1 mL of 1 mol L -1 The sodium ion battery electrolyte is mixed evenly, and its electrolyte is denoted as EDF.
[0055] Electrolyte containing high-purity compound 18
[0056] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.168 g of sodium hexafluorophosphate and dissolve it in 1 mL of a mixed solvent of ethylene carbonate and diethyl carbonate (1:1 by vol.) and stir overnight to fully dissolve and mix well to prepare a 1 mol L -1 Sodium ion battery electrolyte (denoted as ECD).
[0057] 2) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, 10 μL of high-purity compound 18 was mixed with 1 mL of 1 mol L -1 The sodium ion battery electrolyte is mixed evenly, and its electrolyte is denoted as ECDF.
[0058] Electrolyte containing high-purity compound 22
[0059] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.168 g of sodium hexafluorophosphate and dissolve it in 1 mL of a solution of ethylene carbonate, propylene carbonate, diethyl carbonate, and fluoroethylene carbonate (6:6:6:1 by vol.) and stir overnight to fully dissolve and mix well to prepare a 1 mol L -1 Sodium ion battery electrolyte (denoted as Baseline).
[0060] 2) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, 5 μL of high-purity compound 22 was mixed with 1 mL of 1 mol L -1 The sodium ion battery electrolyte is mixed evenly, and the electrolyte is denoted as NFS.
[0061] Electrolyte containing high-purity compound 45
[0062] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.1224 g of sodium perchlorate and dissolve it in 1 mL of a solution of propylene carbonate and fluoroethylene carbonate (9:1 by vol.) and stir overnight to fully dissolve and mix well to prepare a 1 mol L -1 Sodium ion battery electrolyte (denoted as BE).
[0063] 2) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, 10 μL of high-purity compound 45 was mixed with 1 mL of 1 mol L -1 The sodium ion battery electrolyte (BE) is mixed evenly and the electrolyte is denoted as BEM.
[0064] Electrolyte containing high-purity compound 53
[0065] In a glove box at 25 °C with water and oxygen contents below 0.01 ppm, 20 μL of high-purity compound 53 was mixed with 1 mL of 1 mol L -1 The sodium ion battery electrolyte (mentioned above, the Baseline) is mixed evenly, and the electrolyte is recorded as TMS.
[0066] Preparation of NFM111 electrode: NFM111, acetylene black and PVDF binder were dispersed into slurry in a ratio of 8:1:1 by N-methylpyrrolidone (NMP), and evenly coated on aluminum foil with a 100 μm scraper, and then vacuum dried at 80 ° C for 12 h. The aluminum foil coated with the material was cut into electrode sheets with a diameter of 12 mm by a cutting machine and placed in a glove box for use;
[0067] Preparation of NVPF electrode: NVPF, acetylene black and PVDF binder were dispersed into slurry by NMP in a ratio of 8:1:1, and evenly coated on aluminum foil with a 100 μm scraper, and then vacuum dried at 80 ° C for 12 h. The aluminum foil coated with the material was cut into electrode sheets with a diameter of 12 mm using a cutting machine and placed in a glove box for later use;
[0068] Preparation of HC electrode: HC, Super P and PVDF binder were dispersed into slurry by NMP in a ratio of 8:1:1, and evenly coated on aluminum foil with a 50μm scraper. Then, it was vacuum dried at 80℃ for 12h, cut into electrode sheets with a diameter of 12mm, and stored in a glove box.
[0069] In the glove box, the prepared NFM111 and NVPF electrode sheets were used as positive electrodes; HC electrode sheets and sodium sheets with a diameter of 14 mm were used as negative electrodes; glass fiber was used as a separator; EDF, ECDF, NFS, BEM and TMS electrolytes prepared using various sodium-based electrolytes and compounds 7, 18, 22, 45 and 53 as electrolyte additives were used to assemble NFM111||Na, NFVP||Na and NFM111||HC soft-pack batteries. The test data were obtained using an electrochemical test system at 25°C.
[0070] The electrochemical performance of the prepared battery was tested. NFM111 and NVPF were used as positive electrodes, HC and sodium metal were used as negative electrodes, and NFM111||Na, NVPF||Na, and NFPP||HC batteries were assembled with different electrolyte systems at 25°C, and their rate performance and cycle stability were tested.
[0071] At 25°C, 4.3V high voltage and 0.5C discharge rate, NVPF||Na batteries were assembled using ED and EDF electrolytes, and the specific capacity and coulombic efficiency of the batteries were tested. The results are as follows: Figure 1 As shown;
[0072] from Figure 1 It can be seen that under the conditions of 4.3V and 0.5C, the NVPF||Na battery assembled with the EDF electrolyte in Example 1 can stably cycle 1000 cycles with a capacity retention rate of 90.2%, while the capacity retention rate of the NVPF||Na battery using the ED electrolyte is 66.29% after 1000 cycles. It can be seen that the EDF electrolyte exhibits better cycle stability.
[0073] At a high voltage of 4.3V and different rates, NVPF||Na batteries were assembled using ECD and ECDF electrolytes, and the specific capacities of NFM111||Na batteries at different rates were tested. The results are shown in Figure 2. Figure 2 And as shown in Table 1.
[0074] Table 1 Electrochemical performance of NVPF||Na battery in ECD and ECDF electrolytes
[0075]
[0076] from Figure 2 It can be seen from the data in Table 1 that the NVPF||Na battery using ECDF electrolyte exhibits good rate performance.
[0077] Under the conditions of 4V voltage and 1C discharge rate, the NFM111||Na battery was assembled using the Baseline electrolyte and the NFS electrolyte in Example 3, and the specific capacity and coulombic efficiency of the battery with a capacity retention rate of 80% were tested. The results are as follows: Figure 3 shown.
[0078] from Figure 3 It can be seen that under the conditions of 4V and 1C rate, the NFM111||Na battery assembled using the NFS electrolyte in Example 3 still has a capacity retention rate of 80% after 500 stable cycles, while the capacity retention rate of the battery assembled using the Baseline electrolyte is only 80% after 179 cycles. This shows that the NFS electrolyte exhibits better cycle stability.
[0079] Under the conditions of high voltage of 4V and different rates, NFM111||Na batteries were assembled using BE and BEM electrolytes, and the specific capacity of NFM111||Na batteries at different rates was tested. The results are as follows: Figure 4 And as shown in Table 2.
[0080] Table 2 Electrochemical performance of NFM111||Na battery in BE and BEM electrolytes
[0081]
[0082] from Figure 4 From the data in Table 2, it can be seen that the NFM111||Na battery using BEM electrolyte exhibits good rate performance.
[0083] Under the conditions of 3.95V voltage and 0.5C discharge rate, NFM111||HC soft pack battery was assembled using Baseline electrolyte and TMS electrolyte in Example 5, and the specific capacity and coulombic efficiency of the soft pack were tested. The results are as follows: Figure 5 shown.
[0084] from Figure 5 It can be seen that under the conditions of voltage 3.95V and rate 0.5C, the battery assembled with TMS electrolyte showed obvious advantages, with a capacity retention rate of 84.2% after 700 cycles, while the battery with Baseline electrolyte had almost no capacity after more than 100 cycles. This shows that the layered oxide sodium ion soft pack battery assembled with TMS electrolyte has good electrochemical performance.
[0085] In summary, the sulfonamide / sulfonamide ester electrolyte additive of the present invention can remove trace hydrofluoric acid and water present in the battery by introducing an amine group; the introduction of a group containing the F element can form a dense passivation protective film on the surface of the electrode material to isolate the electrolyte and the electrode material from further reaction; the introduction of a sulfonate group can improve the ionic conductivity of the electrolyte and form a low-impedance electrode-electrolyte interface film, thereby obtaining a sodium ion battery electrolyte additive system with both long life and high safety.
[0086] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A sulfonamide / sulfonamide ester additive, characterized in that: It is a compound of the structural formula shown in formula (I): Wherein: R1 is one of C1-C3 fluoroalkyl or fluorinated ether groups; R2 and R3 are each independently one of C1-C3 alkyl or fluorinated alkyl.
2. The sulfonamide / sulfonamide ester additive according to claim 1, characterized in that: The R1 is one of the following groups: R2 and R3 are one of the following groups:
3. The sulfonamide / sulfonamide ester additive according to claim 1 or 2, characterized in that: It is one of the following compounds 1 to 75:
4. Use of the sulfonamide / sulfonamide ester additive as claimed in claim 2 or 3 in a sodium ion battery electrolyte.
5. The use of the sulfonamide / sulfonamide ester additive in sodium ion battery electrolyte according to claim 4, characterized in that: The sodium ion battery electrolyte is added with a sulfonamide / sulfonamide ester additive having a volume fraction of 0.1% to 10%.
Citation Information
Cited By
Sodium ion battery based on donor-receptor coupling effect
CN121394519A
Fluorosulfonamide electrolyte containing ether oxygen and preparation method and application thereof
CN121460715A
Ether oxygen-containing fluorosulfonamide electrolyte, preparation method and application thereof
CN121460715B